Estudo analítico-numérico de freios de estampagem em chapas metálicas - Duarte, Écio Naves (2007)
In order to get a better part quality in sheet metal forming, the rate of the material flow into the die cavity must be efficiently controlled. This control is made by a restraining force supplied either by the blankholder, the drawbeads or both. When the restraining force required is too high, the use of drawbeads is necessary, although excessive deformations may be produced. Some others disadvantages, such as difficulties of adjustment during die try-outs in order to determine the actual Drawbead Restraining Force (DBRF), may also be emphasized. To solve these problems and to reduce the number of die try-outs, which are very time consuming, accurate enough drawbeads concepts are necessary. Aiming to understand the influence of the most important parameters on the DBRF and to establish a pre-estimate DBRF theory, in this study a methodology has been developed using similitude. The data bases were achieved by Finite Element (FE) simulations done with an explicit code. Two different materials were used: A-K Steel and 2036-T4 Aluminum. The results have been compared with experimental databases of Nine(1978, 1982) and with the analytical model of Stoughton(1988). The average of absolute error with respect to experimental data bases was about 6 % and, for those cases studied, the maximum discrepancy was found to be less than 11%. For analytical ones, the average of absolute error was about 5 % and, for the cases studied, the maximum error was about 7%. Predictions made with this approach have a very good precision when compared with analytical and experimental results. For this reason, it was used as a contribution for STAMPACK®, an explicit finit element code used to simulate forming process.